2021
DOI: 10.1063/5.0055575
|View full text |Cite
|
Sign up to set email alerts
|

Binding curve of the beryllium dimer using similarity-transformed FCIQMC: Spectroscopic accuracy with triple-zeta basis sets

Abstract: We demonstrate how similarity-transformed full configuration interaction quantum Monte Carlo (FCIQMC) based on the transcorrelated Hamiltonian can be applied to make highly accurate predictions for the binding curve of the beryllium dimer, marking the first case study of a molecular system with this method. In this context, the non-Hermitian transcorrelated Hamiltonian, resulting from a similarity transformation with a Jastrow factor, serves the purpose to effectively address dynamic correlation beyond the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
2
34
1
Order By: Relevance
“…To obtain the ground state eigenvalue ẼB 0 [u] of a given TC Hamiltonian H[u] B , we use the recently developed similarity transformed full-configuration interaction quantum Monte Carlo (ST-FCIQMC) technique 15,27 which extends the original stochastic projection technique of FCIQMC [28][29][30][31][32][33][34][35] to a non-hermitian and threebody Hamiltonian. The FCIQMC parameters were 10 6 walkers, an initiator threshold of n init = 3 and a semistochastic space of N D = 1000.…”
Section: A Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain the ground state eigenvalue ẼB 0 [u] of a given TC Hamiltonian H[u] B , we use the recently developed similarity transformed full-configuration interaction quantum Monte Carlo (ST-FCIQMC) technique 15,27 which extends the original stochastic projection technique of FCIQMC [28][29][30][31][32][33][34][35] to a non-hermitian and threebody Hamiltonian. The FCIQMC parameters were 10 6 walkers, an initiator threshold of n init = 3 and a semistochastic space of N D = 1000.…”
Section: A Computational Detailsmentioning
confidence: 99%
“…The problems regarding these terms are two-fold: (i) the computation of the intermediate quantities which can be quite demanding and (ii) the computation and storage of all the N 6 integrals. In the context of H[µ] B , point (i) is not really a problem since all intermediate quantities are computed analytically and not numerically in contrast to more complex correlation factors 15,27 pendix of Ref. 26).…”
Section: The "5-idx" Approximation On the Three-body Termmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea goes back to the pioneering work of Boys and Handy and is termed transcorrelation, 58 and it has been recently demonstrated that a combination of the transcorrelation with a stochastic full configuration interaction quantum Monte-Carlo (FCIQMC) [59][60][61] yields very promising results for weakly and strongly correlated systems. [62][63][64][65] Since the Hamiltonian itself is transformed, the transcorrelation approach is not specific for low-order methods and can be used together with any excitation orders. The transcorrelated Hamiltonian has been applied before to linearized coupled cluster with singles and doubles, 66 and for the uniform electron gas for coupled cluster and distinguishable cluster with singles and doubles, 67 however with some approximations to the three-body terms in the transformed Hamiltonian and with a simpler correlation factor.…”
Section: Introductionmentioning
confidence: 99%

Transcorrelated coupled cluster methods

Schraivogel,
Cohen,
Alavi
et al. 2021
Preprint
Self Cite
“…102 We note in passing that the same correction was applied in Ref. 103, where the Be 2 PEC was studied with the transcorrelated FCIQMC method. The counterpoise correction was calculated, at each R Be-Be value, from the tcDMRG energy of the Be atom calculated in the presence of a ghost atom carrying the Be cc-pCVDZ basis placed at R Be-Be .…”
mentioning
confidence: 99%